Proceedings of the Fifth International Conference on Simulation Tools and Techniques 2012
DOI: 10.4108/icst.simutools.2012.247743
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of WAVE 1609.4-based Multi-channel Vehicular Ad Hoc Networks

Abstract: Recently, the IEEE 1609.4 Standard for Wireless Access in Vehicular Environments (WAVE) has been proposed to enhance the performance of vehicular networks with multi-channel operations that allow for the coexistence of safety-related and non-safety related vehicular applications. However, while the benefits of the multi-channel approach are clear, the impact of the IEEE 1609.4 channel scheduler on the performance of delay-constrained vehicular applications remains to be well explored by researchers. At present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…However, the way that is chosen by MAC scheme to switch between multiple defined channels has a great impact on its performance. Many papers evaluated the performance of the multichannel operation of the IEEE 1609.4 protocol to show the impact of alternating nature of the protocol [28][29][30][31][32].…”
Section: Medium Access Control Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the way that is chosen by MAC scheme to switch between multiple defined channels has a great impact on its performance. Many papers evaluated the performance of the multichannel operation of the IEEE 1609.4 protocol to show the impact of alternating nature of the protocol [28][29][30][31][32].…”
Section: Medium Access Control Approachesmentioning
confidence: 99%
“…To this end, a customized simulator using NS-2 was developed and tested, and results were published in [41]. The developed simulator integrates the WAVE1609 [30] and CRCN [42] packages with IEEE 802.11p PHY and MAC standard configuration file [43] based on NS-2.34. The WAVE1609 package provides the multichannel operation of the IEEE 1609.4 standard, while the CRCN package helps definition of multiple channels, and the IEEE 802.11p PHY and MAC standard configuration file configures physical and link layer attributes of each channel.…”
Section: Simulator Developmentmentioning
confidence: 99%
“…These results motivate the need of enhanced MAC contention control mechanisms, that dynamically adapts to the channel decisions performed by the upper WAVE stack. We model a multi-channel VANETs through the ns-2 simulation tool, with the additional extensions for the WAVE protocol stack described in [6]. These extensions provide a realistic modeling of the IEEE 1609.4 multi-channel operations performed by vehicles with a single radio transceiver.…”
Section: Motivationsmentioning
confidence: 99%
“…However, several research papers (e.g. [6] [7] [11] [13]) revealed that halving the available bandwidth might seriously compromise the performance of safety and non-safety vehicular applications over realistic scenarios. In this paper, we investigate the performance of multi-channel IEEE 802.11p/1609.4-based VANETs, and we show that leveraging channel diversity does not always lead to an increase in the performance of wireless systems.…”
Section: Introductionmentioning
confidence: 99%
“…Misic et al (2011) present the analytical model of the IEEE MAC 802.11p. The simulation studies (Chen et al, 2009a;Di Felice et al, 2012a;Ghandour et al, 2012) discuss the synchronisation of the back-off process at the MAC layer caused due to the CCH/SCH switching operation. This result in an increased probability of collisions for beaconing messages transmitted on the control channels.…”
Section: Protocol Enhancement In Transmission Operations At the Mac Lmentioning
confidence: 99%